New spring wheat varieties ‘Panianka’ and ‘Diana’ - О. А. Демидов; С. О. Хоменко; І. В. Федоренко; М. В. Федоренко; Р. М. Близнюк (Plant Varieties Studying and Protection)
Purpose. To create new competitive spring wheat varieties. Methods. Field study, laboratory test. Results. Based on the competitive variety trial, bread spring wheat line ‘Lutescens 07-26’ has been selected due to high values of such traits as resistance to fungal diseases, grain quality(protein content accounted for 15.0%), 1000 kernel weight (44.6 g) productivity (3.92 t/ha) and lodging resistance (9 points). In 2011, it was submitted to the State variety testing as ‘Panianka’ variety. Durum spring wheat line ‘Leukurum 08-11’ was characterized by a number of positive traits: quite a high productivity (3.05 t/ha), short stem (79 cm), resistance to fungal diseases and lodging(9 points), and in 2011 it was submitted to the State variety testing as ‘Diana’ variety. According to the results of the State variety testing in 2012–2014, spring wheat varieties ‘Panianka’ and ‘Diana’ in 2015 were put on the State Register of plant varieties suitable for dissemination in Ukraine. Conclusions. For farms in Forest-Steppe and Polissia zones of Ukraine, bread and durum spring wheat varieties were bred by V. M.Remeslo Myronivka Institute of Wheat of NAAS of Ukraine that demonstrated rather high potential of productivity and adaptability to stress conditions. This goes to prove that cultivation of domestic spring wheat varieties will promote formation of high and quality grain yields.